The modern use of the Bible - Fosdick, Harry Emerson (Lyman Beecher lectureship on preaching, Yale University, 1924)
The new approach to the Bible -- The old Book in a new world -- The ancient solution -- Abiding experiences in changing categories -- Miracle and law -- Perils of the new position --Jesus, the Messiah -- Jesus, the son of God.